THU0536 The AGC Kinases Protein Kinase B (PKB) and Serum and Glucocorticoid Kinase (SGK) Differentially Regulate the Metabolic Activity and Inflammatory Activation of Rheumatoid Arthritis Fibroblast-Like Synoviocytes and Human Macrophages. (10th June 2014) - Hartkamp, L.M.; van Es, I.E.; Malvar Fernandez, B.; Tak, P.P.; Reedquist, K.A.
Abstract : Background: Phosphatidylinositol 3-kinase (PI3K) –dependent activation of PKB, and subsequent PKB phosphorylation and inactivation of FoxO transcription factors, is a critical regulator of cellular proliferation and survival. Constitutive activation of the PI3K/PKB pathway, and inactivation of FoxO proteins is observed in rheumatoid arthritis (RA) patient synovial tissue, and rescue of FoxO1 activity induces RA fibroblast-like synoviocyte (FLS) apoptosis. However, SGK, an AGC kinase related to PKB, can also target the same residues of FoxO proteins. Objectives: Here, we sought to determine the relative contributions of PKB and SGK to RA FLS survival and inflammatory activation. Methods: PKB and SGK isoform expression was detected by qRT-PCR and immunoblotting experiments on isolated cell populations. Effects of specific PKB (Akt inhibitor VIII) and SGK (GSK 650394) inhibitors on metabolic activity and IL6 production was assessed by MTT assay and ELISA, respectively. The influence of pharmacological inhibition of PKB or SGK on expression of IL1 responsive genes in RA FLS and human macrophages was determined using low density qPCR arrays. Furthermore, effects of pharmacological targeting of PKB or SGK on RA FLS IL-1β- or PDGF- induced FoxO1 phosphorylation was assessed by immunoblotting. Results: All PKB isoforms ( AKT1, AKT2, and AKT3 ) were expressed at equivalent levels in RA FLS, while only SGK1 and SGK3, but not SGK2, were detected. PKBi, but not SGKi, significantly decreased FLS mitochondrial activity. In contrast, only SGKi significantly reduced IL-1β-induced IL-6 production. Examining 84 genes induced by IL-1β in RA FLS, we found that PKBi suppressed transcription of CCL7, CXCL6 CXCL9, CXCL10, CXCL11, IL1RN, and MMP13, but enhanced IL23A and TNFα expression. SGKi enhanced EREG expression, but suppressed CXCL10, CCL4, CCL5, CSF3, IL6, MMP3, MMP7 and VCAM1 expression. In human macrophages we found that PKBi suppressed transcription of IL36A and PGLYRP1, SGKi suppressed IL6 and TNF . Neither compound interfered with IL-1β-induced FoxO1 phosphorylation at AGC kinase consensus sites. Conclusions: Our results provide the first evidence for a role of SGK in the inflammatory activation of RA FLS and human macrophages, point to an unidentified third AGC kinase regulating FoxO1, and suggest that targeting distinct PI3K-dependent AGC kinases can preferentially modulate specific components of cellular activation. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5096